Modulation of automatic and creative features of the Remote Associates Test by angular gyrus stimulation. (June 2019) - Pick, Hadas; Lavidor, Michal
Abstract: Creative thinking comprises two main components: divergent and convergent thinking. The Remote Associates Test (RAT) was designed to examine the ability to form associative elements into new combinations, however it is widely used as a general creativity measure, without sub-dividing it to its components. Our goal here was to explore the sub-components of the RAT, aiming to link them to the angular gyrus (AG) activation. The AG seems as a good candidate to host both aspects of the RAT, as neuroimaging studies observed deactivation in the AG while participants were engaged in creative tasks, however it also seems to play a role in arithmetic solution retrieval and automatic knowledge retrieval. Our objective was therefore to test whether transcranial direct current stimulation (tDCS) of the AG will influence creative and automatic performance in the RAT. In Experiment 1, in the creative group we administrated cathodal right AG stimulation in order to deactivate the AG aiming to improve divergent features of the RAT. In the automatic group, we administrated double anodal AG stimulation in order to improve convergent features of the RAT and included a control SHAM condition in each group. Experiment 2 activated the AG by stimulation and arithmetic training. We hypothesized that anodal stimulation of the AG will improve automatic convergent features as in Experiment 1. In addition, we expected the arithmetic training to improve the automatic score in the RAT. In Experiment 1, activation of the AG interrupted creative abilities and enhanced automatic abilities. Additionally, deactivation of the AG enhanced creative abilities reflecting divergent thinking. While in Experiment 2 both stimulation and arithmetic training resulted in higher automatic performance. We argue that the RAT measures automatic rather than creative abilities. Highlights: Anodal stimulation to the Angular gyrus (AG) interrupted divergent thinking and consistently enhanced convergent thinking. Cathodal stimulation to the AG enhanced divergent thinking. RAT task measures automatic rather than creative abilities. Arithmetic training resulted in higher scores in convergent thinking task reflecting AG activation.